Just using computers for any subject is not enough to acquire computational thinking in early childhood education - Hermida, Maria Julia (2022)
In this invited commentary we state whay it is not the same, at the cognitive level, to use computers to teach art than programming and that, if we want children to learn computational thinking, we need to teach them computer science contents.